The Rhythm of Conceptions. Seasonality of Births in Taiwan and the Netherlands, 1800–1940 - Theo Engelen (Historical Life Course Studies)
The seasonality of births provides us with insights into the economic, cultural, and biological effects on the private lives of our predecessors in time. This comparison between two culturally very different societies results in the conclusion that there is an amazing geographic and historical stability in the patterns of seasonality in conceptions, both in Taiwan and in the Netherlands. Economic and cultural variables only have a minor influence. The fact that a biological variable like temperature is so dominant in the Taiwanese case suggests that future studies may benefit from focusing more on the biological determinants of human behaviour.